Gender impacts on motor skill proficiency-physical activity relationship in children - Diana Samara; Nuryani Sidharta; Dian Mediana; Noviyanti Noviyanti (Faculty of Medicine, Universitas Trisakti, 2012)
BACKGROUND Physical activity is the greatest contributor to achievement of adequate physical activity. Children performing adequate daily physical activity will get positive benefits from their activity. Several studies indicate a difference in motor skills between boys and girls. To understand the development of motor skill proficiency and physical activity in boys and girls, a study was conducted to determine the role of gender on motor skill proficiency and physical activity in children aged 6-12 years. METHODS A cross-sectional observational study was conducted and a total of 162 children were included at a primary school in the Grogol area, West Jakarta. Data collection was by questionnaire-based interviews, covering age, gender, and physical activity (watching TV, playing games, and outdoor play). Assessment of motor skills was performed using the Bruininks-Oseretsky Test–Second Edition (BOT-2). Data analysis was performed using SPSS for Windows release 17.0 and level of significance was set at 0.05. RESULTS Multiple linear regression results showed that in boys the strength subset was the most influential factor on TV watching activity, with the higher scores for strength indicating a lower TV watching activity (â=-0.125;p=0.021). Age was the most influential factor on outdoor playing activity in girls, with older girls having lower outdoor playing activity (â=-0.375;p=0.016). CONCLUSIONS This study revealed that gender difference impacts on motor skills and physical activity in children. Higher motor proficiency increases outdoor playing activity only in boys. Primary school pupils should be given opportunities for performing outdoor playing activities to improve their motor proficiency.